Systematic Mapping Study Tourism Business With An Entrepreneurial Marketing Perspective - Adjie Ahmad Darajat; Bambang Hermanto; Arianis Chan (Universitas Winaya Mukti, 2023)
This research aims to explore and categorize existing entrepreneurial marketing in tourism literature to identify the state-of-the-art and research gaps. We conducted a systematic mapping study approach to analyze, categorize and map relevant research areas. The mapping was based on the focus, methods, design, and research trends obtained through the Scopus international publication database. Our mapping found 28 relevant articles out of 367 published from 1986-2021. Our findings suggest that the highest development trend was generated in 2019. Customer orientation is the most common focus. Hospitality became the most popular in this study. Furthermore, evaluation research with a qualitative interview design is the most widely used in this study. We conducted a systematic mapping study to provide an overview and status of the research and serve as a guide to identify state-of-the-art future research .